Recent advances of transition Ir(III) complexes as photosensitizers for improved photodynamic therapy. Issue 6 (21st June 2021) - Zhang, Liping; Ding, Dan
Abstract: Photodynamic therapy (PDT), a minimally invasive procedure, usually required photosensitizer (PS) under light irradiation to convert the absorbed light energy into reactive oxygen species (ROS) to cause cancer cell apoptosis. The PSs with abundant excited triplet state play a critical role to guarantee the PDT effect. Transition Ir(III) complexes has been proved to be an effective PSs for PDT, owing to their high intersystem crossing (ISC) ability, tunable optical properties, long excited state lifetimes. However, poor biocompatibility, short excitation wavelength, and high oxygen dependence limit their biomedical applications. This review summarizes important progress of Ir(III) complexes as PS in improved PDT, including: (1) the strategy of nanoparticles is employed to improve their biocompatibility, and significantly enhance the cellular intracellular efficiency at the same time. (2) Their excitation wavelength is successfully extended by combining fluorophores, forming nanoscale Metal‐Organic frameworks (nMOFs) or two‐photon excited therapy. (3) Their therapeutic effect for antihypoxic tumors is enhanced by constructing mitochondrial‐targeted PS or type I PDT. In addition, simple modification of the precursor is beneficial to obtain a more excellent therapeutic effect. Finally, we brief summarize the current challenges and future research opportunities for Ir(III) complexes in this research field. Abstract : The recent progress of Ir(III) complexes as photosensitizers in improved photodynamic therapy is summarized and the latest strategies for Ir(III) complexes to solve biocompatibility, tissue penetration, and hypoxia are highlighted.